2001
DOI: 10.1002/1522-2675(20010815)84:8<2155::aid-hlca2155>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, NMR-Solution and X-Ray Crystal Structure ofN-Acyl-γ-dipeptide Amides That Form aβII′-Type Turn

Abstract: Conformational analysis of g-amino acids with substituents in the 2-position reveals that an N-acyl-gdipeptide amide built of two enantiomeric residues of unlike configuration will form a 14-membered H-bonded ring, i.e., a g-peptidic turn (Figs. 1 ± 3). The diastereoselective preparation of the required building blocks was achieved by alkylation of the doubly lithiated N-Boc-protected 4-aminoalkanoates, which, in turn, are readily available from the corresponding (R)-or (S)-a-amino acids (Scheme 1). Coupling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…In a previous paper we have shown that simple N ‐acyl‐γ‐dipeptide amides that resemble a βII′ turn of an α‐peptide can be designed to form a turn structure in solution (NMR) and in the solid state (X‐ray) 1. 2 To see whether such a turn could also be used to mimic a peptide, the biological activity of which rests upon a turn structure carrying functionalized side chains, we have now synthesized compounds 1 a – g (Scheme ), with the side chain of tryptophan in the γ 2 position of the first and of lysine in the γ 4 position of the second γ‐amino acid, and have tested their affinities for the human somatostatin receptors hsst 1–5 3–6…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper we have shown that simple N ‐acyl‐γ‐dipeptide amides that resemble a βII′ turn of an α‐peptide can be designed to form a turn structure in solution (NMR) and in the solid state (X‐ray) 1. 2 To see whether such a turn could also be used to mimic a peptide, the biological activity of which rests upon a turn structure carrying functionalized side chains, we have now synthesized compounds 1 a – g (Scheme ), with the side chain of tryptophan in the γ 2 position of the first and of lysine in the γ 4 position of the second γ‐amino acid, and have tested their affinities for the human somatostatin receptors hsst 1–5 3–6…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of γ‐dipeptide derivatives 1 commenced with the N ‐Boc‐γ‐lactams 2 and 3 (Boc= tert ‐butoxycarbonyl), readily available from the corresponding commercial ( R )‐Ala and ( S )‐Lys acids by known procedures 1. 7 Ring opening (with the Lys derivative after change of side‐chain protection, → 4 ), and esterification with Me 3 Si(CH 2 ) 2 OH provided the ( R )‐Boc‐γ 4 ‐hhAla and Boc‐γ 4 ‐hhLys(Bn 2 ) esters, which were doubly deprotonated and alkylated with 1‐mesitylenesulfonyl‐3‐bromomethylindole and MeI to give the unlike γ 2,4 ‐amino acid derivatives 5 and 7 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Reduction of the azide and hydrolysis of the lactam affords (S,S)-a-methyl pregabalin (S,S)-(173) [143]. Alkylation, under a range of conditions, of the enolates of methyl N-protected g-amino esters (174) affords the syn-2,4-disubstituted products (175), through 1,3-asymmetric induction (Scheme 14.49) [144,145].…”
Section: Ab-disubstituted G-amino Acidsmentioning
confidence: 99%
“…In the six years of research on peptides consisting of homologated proteinogenic amino acids we [54][55][56][57][58][59] and others [60][61][62][63][64] have embarked for a trip into an entirely new world, in which almost everything we know about a-peptides had to be disregarded. The homologous peptides form secondary structures, such as helices and turns, with as few as two to six residues [10,12,21,42,58], whereas α-peptides require more than ten residues for helix and turn formation under the same conditions (MeOH solution, NMR detection); parallel [6,21,64] and antiparallel [21,42,58] sheets and stacks (of cyclic ßpeptides [8,22,36,45]) are found in solution and in the solid state ( Figure 6).…”
Section: ß-And γ-Peptides -A Different Worldmentioning
confidence: 99%
“…The homologous peptides form secondary structures, such as helices and turns, with as few as two to six residues [10,12,21,42,58], whereas α-peptides require more than ten residues for helix and turn formation under the same conditions (MeOH solution, NMR detection); parallel [6,21,64] and antiparallel [21,42,58] sheets and stacks (of cyclic ßpeptides [8,22,36,45]) are found in solution and in the solid state ( Figure 6). All of these secondary structures can be designed by choosing the "right" substitution pattern (constitution) and (relative and absolute) configuration of the residues in the ß-and γ-peptidic chains, and MD calculations (GROMOS96 program, including solvent) furnish all the experimentally determined structures within a couple of nanoseconds ("in silico") [18,31,38].…”
Section: ß-And γ-Peptides -A Different Worldmentioning
confidence: 99%